Crystal Structure of the Marburg Virus VP35 Oligomerization Domain - Bruhn, Jessica F.; Kirchdoerfer, Robert N.; Urata, Sarah M.; Li, Sheng; Tickle, Ian J.; Bricogne, Gérard; Saphire, Erica Ollmann (Journal of virology, 2017)
Marburg virus (MARV) is a highly pathogenic filovirus that is classified in a genus distinct from that of Ebola virus (EBOV) (genera Marburgvirus and Ebolavirus , respectively). Both viruses produce a multifunctional protein termed VP35, which acts as a polymerase cofactor, a viral protein chaperone, and an antagonist of the innate immune response. VP35 contains a central oligomerization domain with a predicted coiled-coil motif. This domain has been shown to be essential for RNA polymerase function. Here we present crystal structures of the MARV VP35 oligomerization domain. These structures and accompanying biophysical characterization suggest that MARV VP35 is a trimer. In contrast, EBOV VP35 is likely a tetramer in solution. Differences in the oligomeric state of this protein may explain mechanistic differences in replication and immune evasion observed for MARV and EBOV. IMPORTANCE Marburg virus can cause severe disease, with up to 90% human lethality. Its genome is concise, only producing seven proteins. One of the proteins, VP35, is essential for replication of the viral genome and for evasion of host immune responses. VP35 oligomerizes (self-assembles) in order to function, yet the structure by which it assembles has not been visualized. Here we present two crystal structures of this oligomerization domain. In both structures, three copies of VP35 twist about each other to form a coiled coil. This trimeric assembly is in contrast to tetrameric predictions for VP35 of Ebola virus and to known structures of homologous proteins in the measles, mumps, and Nipah viruses. Distinct oligomeric states of the Marburg and Ebola virus VP35 proteins may explain differences between them in polymerase function and immune evasion. These findings may provide a more accurate understanding of the mechanisms governing VP35's functions and inform the design of therapeutics.